Performance and Health Parameters of Sows and Their Litters Using a Probiotic Supplement Composed of Bacillus subtilis 541 and Bacillus amyloliquefaciens 516 - Aline Maria Silva Barbosa; Maria Paula Souza Carvalho; Luciana de Paula Naves; Stephane Alverina Briguente da Motta; Rhuan Filipe Chaves; Maíra Resende; Daniele de Lima; Lea Hübertz Birch Hansen; Vinícius de Souza Cantarelli (Animals)
This study investigated the efficacy of using probiotics on the performance and health parameters of sows and their litters. A randomized block design was used with 584 sows and 292 replications, with two dietary treatments: the control group (basal diet without probiotics) and the probiotic group (basal diet supplemented with 400 g/ton of a probiotic composed of Bacillus subtilis (B. subtilis) 541 and Bacillus amyloliquefaciens (B. amyloliquefaciens) 516). Feed intake was evaluated throughout the experimental period. Bodyweight and backfat thickness of the sows were measured at the beginning and end of each phase. Piglets were weighed individually at birth and at weaning. Performance variables and physiological parameters were analyzed. Sows that received the probiotic supplement exhibited increased milk production (p = 0.05) and bodyweight loss, along with reduced postpartum cortisol levels (p < 0.05). The piglets from the probiotic treatment group had higher (p < 0.001) weaning weight and fewer (p < 0.05) crushing deaths, received fewer (p < 0.001) medications, and had lower (p < 0.05) excretion of pathogenic bacteria and lower (p < 0.05) excretion of fecal Lactobacillus sp. They also had higher (p < 0.05) concentration of fecal myeloperoxidase (MPO) close to weaning and improved ileal histomorphometric measures. In conclusion, supplementation with the probiotic product improves performance and promotes health parameters of the sows their litters.